2017
DOI: 10.1111/odi.12687
|View full text |Cite
|
Sign up to set email alerts
|

Sporadic versus syndromic keratocysts—Can we predict treatment outcome? A review of 102 cysts

Abstract: Postsurgical complications may be expected in: older patients, upper jaw location, extensive lesions, and sporadic KCOT. Most KCOT recurrence is diagnosed 3 years from treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 18 publications
0
17
0
4
Order By: Relevance
“…This syndrome is an autosomal dominant inherited condition that exhibit many specific features including multiple OKCs [12]. Noy et al described the recurrence rate of syndromic OKCs compared with sporadic OKCs and observed that there was a 3.4 times increased risk of developing recurrence in patients affected by Gorlin Goltz syndrome independently from the kind of treatment performed [12]. This increased tendency to relapse in syndromic lesions may represent a bias of this study influencing the results.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…This syndrome is an autosomal dominant inherited condition that exhibit many specific features including multiple OKCs [12]. Noy et al described the recurrence rate of syndromic OKCs compared with sporadic OKCs and observed that there was a 3.4 times increased risk of developing recurrence in patients affected by Gorlin Goltz syndrome independently from the kind of treatment performed [12]. This increased tendency to relapse in syndromic lesions may represent a bias of this study influencing the results.…”
Section: Discussionmentioning
confidence: 86%
“…In our study, Carnoy's solution was used only in patients with Gorlin Goltz syndrome in which a preoperative diagnosis of odontogenic keratocyst has been done. This syndrome is an autosomal dominant inherited condition that exhibit many specific features including multiple OKCs [12]. Noy et al described the recurrence rate of syndromic OKCs compared with sporadic OKCs and observed that there was a 3.4 times increased risk of developing recurrence in patients affected by Gorlin Goltz syndrome independently from the kind of treatment performed [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Porém, foi descrito com detalhes histológicos apenas em 1970 e 1971 com as publicações de Browne. Este autor detalhou características histológicas importantes, bem como a sua alta capacidade de recidiva (Noy, Rachmiel, Zar, Emodi, & Nagler, 2017).…”
Section: Introductionunclassified
“…Sabe-se que o ceratocisto tem origem histológica dos restos celulares da lâmina dentária. Este cisto, diferentemente de outras entidades císticas, parece ter seu crescimento associado tanto a pressão osmótica como a fatores enzimáticos ligados a própria parede cística, fatos que levaram a ser considerado como uma lesão neoplásica até um passado recente (Noy, Rachmiel, Zar, Emodi, & Nagler, 2017).…”
Section: Introductionunclassified